2020
DOI: 10.1111/ics.12661
|View full text |Cite
|
Sign up to set email alerts
|

Measurements meet perceptions: rheology–texture–sensory relations when using green, bio‐derived emollients in cosmetic emulsions

Abstract: ObjectiveProduct aesthetics and sensory performance can strongly influence a cosmetic product’s acceptance by consumers. However, classic sensory analysis is time‐consuming, expensive and does not provide information on the target group’s preference. In the previous phase of this project, we had untrained consumers evaluate six cosmetic emulsions based on their aesthetics using a check‐all‐that‐apply (CATA) survey. In this project, our goals were to quantitatively characterize the rheology and textural propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 17 publications
0
15
1
Order By: Relevance
“…Several authors have in fact made successful attempts to connect physical characteristics of topical formulations to certain sensory attributes. Some of the methods that have been linked to sensory attributes are rheology (Greenaway, 2010;Huynh et al, 2021;Lee et al, 2021;Lukic et al, 2012;Savary et al, 2019;Vergilio et al, 2021), frictional analysis (Lee et al, 2021;Savary et al, 2019;Skedung et al, 2016;Timm et al, 2012) and texture analysis (Huynh et al, 2021;Lee et al, 2021;Savary et al, 2019;Vergilio et al, 2021). Rheology was found to be a useful tool to predict sensory attributes related to the application phase of cosmetic emulsions (Lee et al, 2021;Savary et al, 2019), while texture analysis was found to be a good predictor of textural attributes comprising stickiness and firmness (Lee et al, 2021;Savary et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have in fact made successful attempts to connect physical characteristics of topical formulations to certain sensory attributes. Some of the methods that have been linked to sensory attributes are rheology (Greenaway, 2010;Huynh et al, 2021;Lee et al, 2021;Lukic et al, 2012;Savary et al, 2019;Vergilio et al, 2021), frictional analysis (Lee et al, 2021;Savary et al, 2019;Skedung et al, 2016;Timm et al, 2012) and texture analysis (Huynh et al, 2021;Lee et al, 2021;Savary et al, 2019;Vergilio et al, 2021). Rheology was found to be a useful tool to predict sensory attributes related to the application phase of cosmetic emulsions (Lee et al, 2021;Savary et al, 2019), while texture analysis was found to be a good predictor of textural attributes comprising stickiness and firmness (Lee et al, 2021;Savary et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Lukic et al 34 have found a direct correlation between textural parameters of consistency and cohesiveness with maximal and minimal viscosity and G′/G″ obtained from the rheological analysis. Another study confirmed the direct correlation of firmness with viscosity and G′ and the negative correlation between adhesiveness with firmness, G′, and a viscosity 35 . Nevertheless, despite the correlations found between certain textural and rheological parameters, the accuracy of the latter is well documented, especially when studying structural changes over time 36 .…”
Section: Resultsmentioning
confidence: 70%
“…Another study confirmed the direct correlation of firmness with viscosity and G′ and the negative correlation between adhesiveness with firmness, G′, and a viscosity. 35 Nevertheless, despite the correlations found between certain textural and rheological parameters, the accuracy of the latter is well documented, especially when studying structural changes over time. 36 Therefore, the examined rheological behavior in this study could provide a better understanding of the thermal stability of sunscreen formulation with GSE.…”
Section: Texture Profilementioning
confidence: 99%
“…In this sense, specific tests have been developed for the complete assessment of those products. Thus, specific sensorial characteristics can be predicted by interpretation of the physical-mechanical parameters recorded through rheological and texture analysis measurements [ 14 , 54 , 55 ].…”
Section: Methodsmentioning
confidence: 99%